PURWARUPA OTOMATISASI ROBOT LENGAN BERBASIS KOMPUTER - , NIRWAN PRANEDYA PRATAMA; , Raden Sumiharto, S.si. M.kom. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of technology as a product of the increasingly advancing human civilization has been perceived as being very much helpful in facilitating humans fulfilling their life needs in such a modern age as now. The increasingly sophisticated technology laboratory holds a prominent role in the process of improving the results of a particular activity. Automation prototype robot arm with computer is evolution from prototype before which using manual control. This prototype still using principle of H-Bridge that using 12 volt DC motor and 12 volt DC motor driver. The prototype can still also be controlled by using the interface made by utilizing the Visual Basic 6.0 software. As for the communication system between the microcontroller and the computer, serial communication system is used, by USB prolific which can be directly connected to Serial of microcontroller. The result of the test shows that this system of the Automation prototype robot arm works can be controlled via computer. Thatâs movement are movement up and down. The Sytem has been applied by carring three taste censor which can be move up and down in automatic mode.